2022
DOI: 10.1111/1471-0528.17303
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical and neonatal complications in hereditary haemorrhagic telangiectasia: A retrospective study

Abstract: Objective To retrospectively describe a large series of pregnancies in women with hereditary haemorrhagic telangiectasia followed in our reference centre, plus neonatal outcomes, to better understand the risks of complications and to improve their prevention. Design A retrospective descriptive study conducted through a phone questionnaire. Setting Reference centre for hereditary haemorrhagic telangiectasia in Lyon, France. Population Women meeting the following criteria: (1) alive and aged ≥18 years; (2) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…HHT is often diagnosed during pregnancy, mainly in the 3rd trimester or after delivery. Most pregnancies are uneventful, but there is a significant maternal risk of arteriovenous malformation rupture [ 60 ]. The Curaçao Diagnostic Criteria are usually used for diagnosis, including the family and personal clinical history associated with findings of diffuse telangiectasias and shunts, heterogeneous liver enhancement, and a common hepatic artery > 6 mm in diameter to confirm the diagnosis [ 33 , 59 , 60 ] (Fig.…”
Section: Liver Diseases Exacerbated By or More Frequent During Pregnancymentioning
confidence: 99%
“…HHT is often diagnosed during pregnancy, mainly in the 3rd trimester or after delivery. Most pregnancies are uneventful, but there is a significant maternal risk of arteriovenous malformation rupture [ 60 ]. The Curaçao Diagnostic Criteria are usually used for diagnosis, including the family and personal clinical history associated with findings of diffuse telangiectasias and shunts, heterogeneous liver enhancement, and a common hepatic artery > 6 mm in diameter to confirm the diagnosis [ 33 , 59 , 60 ] (Fig.…”
Section: Liver Diseases Exacerbated By or More Frequent During Pregnancymentioning
confidence: 99%
“…Dear Dr Papageorghiou, We appreciate the unique study by Delagrange et al 1 reporting the largest ever series of pregnancies in women with hereditary haemorrhagic telangiectasia (HHT) treated in their institute over a large time frame. The authors have taken the initiative to compare the data extracted from the retrospective chart review with the responses obtained from telephonic conversations.…”
Section: The Challenges Of Pregnancy With Hereditary Haemorrhagic Tel...mentioning
confidence: 99%
“…The data that support the findings of this study are available from the corresponding author upon reasonable request. 1 In the article, we retrospectively described a large series of pregnancies in women with hereditary haemorrhagic telangiectasia followed in our reference centre plus neonatal outcomes, to better understand the risks of complications and to improve their prevention. Our findings indicated that severe complications during pregnancy or delivery in HHT are rare.…”
Section: Data Ava I L a Bi L I T Y S Tat E M E N Tmentioning
confidence: 99%
“…To our knowledge, Joel Agarwal et al [23] summarized the information of 8 non-case studies and 15 case studies from MEDLINE and EMBASE about HHT patients with PAVM and neurological complications, including ischemic stroke and transient ischemic attack (TIA). Then we here provided both non-case studies (Table 1) [24][25][26][27][28][29][30] and case studies (Table 2) [31][32][33] related to HHT patients with PAVM-induced ischemic stroke from 2017 to 2023. The non-case studies we showed in Table 1 were found tended to discuss the correlation between PAVM and stroke in general or PAVM population, rather than in the HHT cohorts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study also showed no correlation between the characteristics of PAVM and the severity of TIA or stroke, while Johan Etievant et al [28] held the opposite opinion. Additionally, patients with HHT-related PAVM had a greater rate of ischemic stroke than the general population [26, 28, 29], which was supposed to be attached importance to particularly during pregnancy or postpartum in women [24]. HHT can lead to various symptoms, thus usually involving a great many clinical departments.…”
Section: Literature Reviewmentioning
confidence: 99%